Analog VLSI : circuits and principles - Liu, Shih-Chii. (Cambridge, Mass. : MIT Press, 2002)
Neuromorphic engineers work to improve the performance of artificial systems through the development of chips and systems that process information collectively using primarily analog circuits. This book presents the central concepts required for the creative and successful design of analog VLSI circuits. The discussion is weighted toward novel circuits that emulate natural signal processing. Unlike most circuits in commercial or industrial applications, these circuits operate mainly in the subthreshold or weak inversion region. Moreover, their functionality is not limited to linear operations, but also encompasses many interesting nonlinear operations similar to those occurring in natural systems. Topics include device physics, linear and nonlinear circuit forms, translinear circuits, photodetectors, floating-gate devices, noise analysis, and process technology.
1. Introduction -- I. Silicon and Transistors -- 2. Semiconductor Device Physics / Jorg Kramer -- 3. MOSFET Characteristics / Shih-Chii Liu and Bradley A. Minch -- 4. Floating-Gate MOSFETs / Chris Diorio -- II. Statics -- 5. Basic Static Circuits / Jorg Kramer -- 6. Current-Mode Circuits / Giacomo Indiveri and Tobias Delbruck -- 7. Analysis and Synthesis of Static Translinear Circuits / Bradley A. Minch -- III. Dynamics -- 8. Linear Systems Theory / Giacomo Indiveri -- 9. Integrator-Differentiator Circuits / Giacomo Indiveri and Jorg Kramer -- 10. Photosensors / Jorg Kramer and Tobias Delbruck -- IV. Special Topics -- 11. Noise in MOS Transistors and Resistors / Rahul Sarpeshkar, Tobias Delbruck, Carver Mead and Shih-Chii Liu -- 12. Layout Masks and Design Techniques / Eric Vittoz, Shih-Chii Liu and Jorg Kramer -- 13. A Millennium Silicon Process Technology / Albert Bergemont, Tobias Delbruck and Shih-Chii Liu.
Includes bibliographical references (pages 415-428) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Integrated circuits -- Very large scale integration; Linear integrated circuits; Circuits intégrés à très grande échelle.; Circuits intégrés linéaires.; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- VLSI & ULSI; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Logic; COMPUTERS -- Logic Design; Integrated circuits -- Very large scale integration; Linear integrated circuits; COMPUTER SCIENCE/General